2022
DOI: 10.3390/ijerph19116916
|View full text |Cite
|
Sign up to set email alerts
|

The Association between mHealth App Use and Healthcare Satisfaction among Clients at Outpatient Clinics: A Cross-Sectional Study in Inner Mongolia, China

Abstract: Mobile health (mHealth) applications (apps) have been developed in hospital settings to allocate and manage medical care services, which is one of the national strategies to improve health care in China. Little is known about the comprehensive effects of hospital-based mHealth app use on client satisfaction. The aim of this study was to determine the relationship between the full range of mHealth app use and satisfaction domains among clients attending outpatient clinics. A cross-sectional survey was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Based on these two points, the researcher conducted an extensive survey on patient satisfaction in terms of meeting patient needs and improving communication skills. The main topics covered were communication attributes (10,11), technical skills of staff (12,13), cost of care (14, 15), waiting time (16,17), hospital hygiene and facilities (18,19), etc. Although these components are somewhat effective in predicting and examining the level of patient satisfaction, however, we found that there are still some shortcomings in these surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these two points, the researcher conducted an extensive survey on patient satisfaction in terms of meeting patient needs and improving communication skills. The main topics covered were communication attributes (10,11), technical skills of staff (12,13), cost of care (14, 15), waiting time (16,17), hospital hygiene and facilities (18,19), etc. Although these components are somewhat effective in predicting and examining the level of patient satisfaction, however, we found that there are still some shortcomings in these surveys.…”
Section: Introductionmentioning
confidence: 99%
“…The result is in line with some other research results indicating that personal experiences of eHealth can predict a degree of eHealth usage [ 21 , 22 ]. Contrarily, absence of associations between satisfaction with eHealth services and eHealth usage have also been described [ 23 ]. Differences between results could be attributed to various target groups, settings, and types of eHealth interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The management of the m-Health platforms plays a significant role in the effective operations of m-Health services [17] and in developing consumer trust [21]. In fact, the recent studies show that the use of m-Health applications could improve patient satisfaction in terms of convenience, health information sharing, and the transparency of medical service fees [22]. Individual users rely on cognitive and emotional trust when making decisions [10].…”
Section: Introductionmentioning
confidence: 99%